Does transition through menopause affect cardiovascular disease risk factors? Results from a population-based cohort (CoLaus study). (14th October 2021) - Raguindin, P F; Cardona, I; Muka, T; Lambrinoudaki, I; Gebhard, C; Franco, O H; Marques-Vidal, P; Glisic, M
Abstract: Introduction: Menopause has been associated with adverse cardiovascular disease (CVD) risk profile, yet it is unclear whether the changes in CVD risk factors differ by reproductive stage independently of underlying aging trajectories. We examined whether reproductive stages are differently associated with changes in cardiovascular risk factors. Methods: This is a prospective population-based cohort study. We used data from women at baseline and follow-up (mean 5.5 years). We classified women into (i) premenopausal, (ii) menopausal transition, (iii) early (≤5 years), and (iv) late (>5 years) postmenopausal by comparing their menstruation status at baseline and follow-up. In the cross-sectional analysis, we compared CVD risk factors at baseline across different reproductive stages using multivariable linear regression models. In the longitudinal analysis, we used multivariable linear mixed models. We used premenopausal women as a reference category and adjusted our analyses for age, medications, hormone replacement therapy, lifestyle, body mass index (BMI) at baseline and follow-up. Results: We used the data from 2, 558 women aged 35–75 years. At baseline, compared to premenopausal women, (i) transition and early postmenopausal groups had higher HDL, (ii) early- and late postmenopausal women had higher BMI, total cholesterol, adiponectin, and interleukin-6 levels, and (iii) all other women groups had higher diastolic blood pressure and glucose levels, while no differences were observed in the other CVD risk factors. At follow-up, women across the four reproductive categories showed an increase in BMI, total cholesterol, triglycerides, and fasting glucose compared to baseline. However, linear mixed models showed that, the changes in CVD risk factors were not significantly different in the other three menopausal categories compared to premenopausal women. When using age as a predictor variable and adjusting for menopause status, most of the CVD risk factors increased, while interleukin 6 and interleukin 1b decreased with advancing age. The estimates did not change when the analyses were restricted to women who did not report hormone therapy-use. Conclusion: The current study suggests that women have a worsening of cardiovascular risk profile as they age, and although menopausal women may have higher levels of cardiovascular risk factors compared to premenopausal women at any given time, the five year changes in cardiovascular risk factors may not depend on menopausal status per se. More studies are still needed to disentangle the contribution of age and menopause in postmenopausal CVD risk, and other pathways not explored in this study. Funding Acknowledgement: Type of funding sources: Other. Main funding source(s): COLAUS was supported by a research grants from GlaxoSmithKline and the Swiss National Science Foundation and